2020
DOI: 10.1111/tbed.13698
|View full text |Cite
|
Sign up to set email alerts
|

The use of facemasks may not lead to an increase in hand–face contact

Abstract: Advocacy of the use of facemasks by the public as a measure against the spread of COVID‐19 is controversial, with some healthcare professionals arguing that the use of a face mask may increase the rate at which people touch their faces, due to readjusting the mask. We assessed the facial touching behaviour of bus passengers in China before and after the outbreak of COVID‐19 and found that wearing a face mask does not increase the number of hand‐face contacts and is likely, therefore, to have a positive benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 7 publications
4
22
0
Order By: Relevance
“…Our results correspond with the prior studies, which either report no association (4,5) or a negative association (7), especially with respect to t-zone touches (6). Taken as a whole, current and prior evidence alleviate the concern that mask-wearing has a positive and adverse face-touching effect (3).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results correspond with the prior studies, which either report no association (4,5) or a negative association (7), especially with respect to t-zone touches (6). Taken as a whole, current and prior evidence alleviate the concern that mask-wearing has a positive and adverse face-touching effect (3).…”
Section: Discussionsupporting
confidence: 90%
“…These results yield additional and robust evidence in favor of the result found in Study 1 and replicated in Study 2: Mask-wearing has a negative relationship with direct hand-to-face contact, while mask-wearing is not associated with touching of the facial region, whether mask covered or not. 5 Figure 1. Sign and significance rates across the multiverse of data and model specifications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other possible causes of the latter include discomfort associated with mask wearing, exacerbation of pre-existing acne, occupational dermatitis, seborrheic dermatitis or rosacea [ 23 , 24 , 25 , 26 ]. Nonetheless, certain studies demonstrated that wearing face masks tends to decrease face touching behaviors, both in the general public [ 27 , 28 ] and also in HCW [ 29 ]. Additionally, the self-reported prevalence of sensitive skin, acne and atopic predisposition in our cohort was similar to other epidemiological studies [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%